Signs of life : a memoir - Taylor, Natalie (Natalie Kelland) (Broadway Books, 2011)
Twenty-four-year-old Natalie Taylor was leading a charmed life. She had a fulfilling job as a high school English teacher, a wonderful husband, a new house and a baby on the way. Then, while visiting her sister, she gets the news that her husband, Josh, has died in a freak accident. What follows is an incredibly powerful emotional journey, as Natalie calls upon resources she didn<U+2019>t even know she had in order to re-imagine and re-build a life for her and her son. In vivid and immediate detail, Natalie documents her life from the day of Josh<U+2019>s death through the birth their son, Kai, as she struggles in her role as a new mother where everyone is watching her for signs of impending collapse. With honesty, raw pain, and most surprising, a wicked sense of humor, Natalie recounts the agonies and unexpected joys of her new life.